2021
DOI: 10.3390/agriculture11121240
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency and Technological Gaps of Rice Production in Anambra State, Nigeria

Abstract: The traditional approach to modeling productive efficiency assumes that technology is constant across the sample. However, farms in different regions may face different production opportunities, and the technologies they employ may differ due to environmental factors. Therefore, rather than using a traditional stochastic frontier model in such cases, a stochastic meta-frontier (SMF) analysis is recommended to account for environmental factors between regions. It follows that differences in environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Under decreasing returns to scale, the farmers could not achieve the equivalent increase in output with the proportionate increase in the input. However, decreasing returns to scale means that the farms still have the opportunity to increase their production portfolios before reaching their full output potential by reducing their production costs without affecting much production [42].…”
Section: Resultsmentioning
confidence: 99%
“…Under decreasing returns to scale, the farmers could not achieve the equivalent increase in output with the proportionate increase in the input. However, decreasing returns to scale means that the farms still have the opportunity to increase their production portfolios before reaching their full output potential by reducing their production costs without affecting much production [42].…”
Section: Resultsmentioning
confidence: 99%
“…The coefficient of age, family size, and extension contact were negative, suggesting that each of these variables could reduce inefficiency by its corresponding coefficient. Ng'ombe [95]; Obianefo et al [96] revealed that gender, farming experience, and interaction with extension agents were among the socioeconomic variables that influenced technical inefficiency. The positive sign of years of experience was probably because, as years of experience increase, age also increases, and farmers are more likely to become conservatives, unwilling to accept modern farming practices.…”
Section: Discussion Of Major Findingsmentioning
confidence: 99%
“…Nigeria until the rice importation ban of 2016, imports most of its rice from Thailand, India and USA, incurring a bill of about N300 million annually in foreign reserves (Osabuohien et al, 2018). The banning of rice importation was to encourage production and consumption of local rice, with simultaneous effect of raising the price of local rice (Obianefo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%